Expression of genes and enzymes involved in ovarian steroidogenesis in relation to human follicular development - Zheng, Mengxue; Andersen, Claus Yding; Rasmussen, Frida Roikjer; Cadenas, Jesús; Christensen, Søren Tvorup; Mamsen, Linn Salto (Frontiers in Endocrinology, 2023)
Granulosa cells (GCs) and theca cells (TCs) play a pivotal role in human ovarian steroidogenesis, facilitating the conversion of cholesterol into sex steroids that regulate normal reproductive function. This study aims to explore the expression patterns of key enzymes that govern human ovarian steroidogenesis throughout follicle development, employing both genomic and immunological methodologies. Follicles and GCs obtained from women undergoing ovarian tissue cryopreservation (OTC) and in vitro fertilisation treatment were utilized. Gene expression data were obtained from a Chinese study using RNA sequencing and from microarray data generated in our laboratory to comprehensively analyse gene expression profiles across distinct stages of follicular development. To corroborate the localization of key enzymes within GCs and TCs, immunohistochemistry analyses utilizing colourimetric and fluorescent techniques were conducted. Steroidogenesis-related enzymes displayed low gene expression levels during early follicle development. However, a notable upregulation of HSD3B2 was observed in GCs as follicles progressed to the antral/preovulatory stage, confirmed consistently using both microarray and RNA sequencing methodologies. Furthermore, immunohistochemical analyses effectively demonstrated that HSD3B2 were not only expressed in GCs, but co-localized with CYP17A1 within a specific subset of TCs surrounding human small antral follicles. Contributing to an enhanced progesterone production during the second half of the follicular phase was a significant upregulation of CYB5A in both microarray and RNA-seq datasets as follicles transition from the antral stage to the pre-ovulatory stage. Moreover, an augmented expression of DHCR24 and LDLR in both types of data, along with HMGCR expression in the microarray data, indicates increased substrate availability for ovarian steroidogenesis. This study confirms and extends that GCs gradually augment expression of HSD3B2 thereby enhancing their capacity for progesterone synthesis as follicles reach the size of selection at around 10 mm in diameter. This is supported by the expression CYB5A and possibly augmented availability of steroid precursors. A subset of TCs exhibit concurrent expression of CYP17A1 and HSD3B2, collectively contributing to the synthesis of 17hydroxyprogesterone. These data significantly enhance our understanding of the dynamic regulation of progesterone throughout the process of follicular development.